Xylitol production by cyberlindnera (Williopsis) saturnus, a tropical mangrove yeast from xylose and corn cob hydrolysate - Kamat, S.; Gaikwad, S.; Kumar, A. Ravi; Gade, Wasudeo N. (Journal of Applied Microbiology, 2013)
AimPotential for xylitol production from xylose and corn cob hydrolysate by a tropical mangrove yeast. Methods and ResultsIn the present study, 21 fungi were isolated from detritus-based mangrove wetlands along the Indian west coast. Of these, one yeast isolate had the ability to grow and assimilate xylose producing significant amounts of xylitol (3863gl(-1)). A maximum yield of 054gg(-1) was obtained after 144h of growth on xylose (150gl(-1)) and corn cob hydrolysate (CCH, containing 65gl(-1) xylose). Using biochemical and molecular methods, the yeast was identified as Cyberlindnera (Williopsis) saturnus. Preliminary characterization of enzymes in the cell-free extract revealed that while xylose reductase (XR) preferred NADPH to NADH as cofactor, xylitol dehydrogenase (XDH) was NAD specific. ConclusionsSignificant amounts of xylitol could be produced on CCH using C.saturnus isolated from tropical mangrove wetlands. The yeast has the potential to assimilate rather than ferment xylose as its XR has a preference for NADPH. Significance and Impact of the StudyMicrobes offer an economically viable and green approach for production of xylitol, an industrially important compound. A mangrove ecosystem with its battery of lignocellulolytic enzymes is an ideal location for isolating fungi capable of producing xylitol from agroindustrial waste such as CCH.
Keywords: corn cob hydrolysate; Cyberlindnera; mangrove; Williopsis; xylitol; Xylose; Yeast

Effect of orifice shape on water disinfection efficacy - Gaikwad, V.; Gaikwad, S.; Ranade, V. (Pollution Research, 2016)
Hydrodynamic cavitation offers distinct advantages for water disinfection and waste watei treatment particularly at large scales of operations. For applying hydrodynamic cavitation foi water disinfection/treatment, water stream to be treated is passed through a fluidic device ir which there exists a low pressure region. Cavities are generated in this region when the pressurt falls below vapour pressure (in absence of any dissolved gases). These cavities are then collapsec when they travel to regions of higher pressure and lead to very high shear, temperatures anc pressures in localized regions. These high pressure/temperature as well as high shear facilitati disinfection as well as reduction in chemical oxygen demand, colour and amonical nitrogen in the water. In this work, we have investigated hydrodynamic cavitation generated by five difieren orifices have been studied which have different shapes with same fractional open area and have tested their effectiveness for water disinfection. The efficacy of generated cavitation on wate disinfection was quantified based on measurements of non-pathogenic E. coli colony forminj units (CFU/mL). The presented results and analysis will be useful for designing hydrodynamii cavitation based systems for water disinfection